From randomized clinical trials to real life data. An Italian clinical experience with ixekizumab and its management. Issue 3 (21st April 2019) - Damiani, Giovanni; Conic, Rosalynn R. Z.; Pigatto, Paolo D. M.; Bragazzi, Nicola L.; Pacifico, Alessia; Malagoli, Piergiorgio
Abstract: Interleukin(IL)‐17 inhibitors display higher efficacy than both TNFi and IL‐12/23i, which increased the goal psoriasis area severity index (PASI) from 75 to PASI 90 or even PASI 100. Ixekizumab, a recombinant, humanized IgG4 monoclonal antibody targeting IL‐17A displayed a high efficacy and safety in RCTs, namely UNCOVER‐2 and UNCOVER‐3. However, few studies examined real‐life data for these medications, and those which exist highlight discrepancies in efficacy and safety between RCTs and real‐life data, likely due to the heterogeneity of patients treated outside of trials. Thus, we performed a single center large prospective observational study (RLSD) that enrolled 47 psoriatic patients followed for 20 weeks and we compared the obtained data with the UNCOVER studies. At week 20 in RLSD versus UNCOVER‐3 both PASI‐90 and PASI‐100 results were similar, whilst at week 12, the RLSD cohort obtained higher PASI 90 (76 vs 69, 3%) and PASI‐100 (55 vs 39%) than UNCOVER cohorts. Interestingly we also reported higher injection‐site related pain that disappeared after week 12. In conclusion, real‐life data together with RCTs contribute to enrich the information background available to dermatologists in daily practice.